Pemberdayaan Digitalisasi UMKM sebagai Anggota Koperasi Desa Merah Putih dalam Meraih Keberhasilan Usaha - Awa Awa; Tini Kartini; Didi Didi; Erny Amriani Asmin; Dwi Gemina; Yulianingsih Yulianingsih; Yoyok Priyo Hutomo (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
In an increasingly disruptive era, businesses have yet to keep pace with the level of competition, particularly in digitalization. Their businesses remain traditional and conventional, necessitating solutions to achieve the desired success. The purpose of this Community Service program is to empower the digitalization of micro, small and medium enterprises (MSMEs) as members of the Koperasi Desa Merah Putih (KDMP) in achieving business success, in Bojong Koneng Village, Babakan Madang District, Bogor Regency. The utilization of digital platforms includes: digital training/competency (Canva, CapCut); digital marketing for social media (TikTok, Instagram) and marketplaces (Shopee, Tokopedia); and digital finance (simple bookkeeping, the BukuWarung app, and digital payments using QRIS). This Community Service activity aims to address these challenges. Empowerment is carried out to increase the understanding of MSMEs as members of the KDMP in carrying out digitalization as well as practicing it using several digital platforms, so they can compete with other competitors in achieving business success. The activity method is carried out in several stages, namely: planning, socialization, workshop, technology implementation, mentoring and evaluation, and program sustainability. The results of this Community Service are characterized by the enthusiasm and ability of MSMEs in receiving materials and being able to practice utilizing digital platforms. This Community Service is very important, impactful, and beneficial for MSMEs, especially in Bojong Koneng village. This research can be used as a guide by academics, business actors, and stakeholders, and it is hoped that in the future research can be conducted in other fields and sectors.